The Role of Immune Checkpoint Inhibition in the Treatment of Brain Tumors - Luksik, Andrew S. (Neurotherapeutics, 2017)
The standard of care for malignant gliomas of the brain has changed very little over the last few decades, and does not offer a cure for these rare, but fatal, tumors. The field of immunotherapy has brought potent new drugs into the oncological armamentarium, and is becoming recognized as a potentially important arm in the treatment of glioblastoma for adults. Immune checkpoints are inhibitory receptors found on immune cells that, when stimulated, cause those immune cells to become quiescent. While this is a natural mechanism to prevent excessive inflammatory damage and autoimmunity in otherwise healthy tissues, cancer cells may utilize this process to grow in the absence of targeted immune destruction. Antibodies derived to block the stimulation of these negative checkpoints, allowing immune cells to remain activated and undergo effector function, are a growing area of immunotherapy. These therapies have seen much success in both the preclinical and clinical arenas for various tumors, particularly melanoma and nonsmall-cell lung cancer. Multiple clinical trials are underway to determine if these drugs have efficacy in glioblastoma. Here, we review the current evidence, from early preclinical data to lessons learned from clinical trials outside of glioblastoma, to assess the potential of immune checkpoint inhibition in the treatment of brain tumors and discuss how this therapy may be implemented with the present standard of care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-017-0513-3) contains supplementary material, which is available to authorized users.